2019
DOI: 10.1002/hed.25779
|View full text |Cite
|
Sign up to set email alerts
|

Trimodality therapy for oropharyngeal cancer in the TORS era: Is there a cohort that may benefit?

Abstract: Background With increasing adoption of transoral robotic surgery (TORS) for oropharyngeal cancer (OPC), more patients may receive trimodality therapy. We sought to investigate outcomes and toxicities in this cohort. Methods A retrospective study of patients with OPC treated with trimodality therapy at a tertiary‐care hospital, comparing those receiving bilateral vs unilateral neck radiation. Results Four hundred thirty‐six patients underwent TORS, 17% receiving adjuvant chemoradiation. Of the 46 patients compl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
18
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(20 citation statements)
references
References 43 publications
2
18
0
Order By: Relevance
“…A total of 12 studies included extractable data on margin status after resection using TORS [ 12 , 26 , 27 , 28 , 29 , 30 , 31 , 32 , 33 , 34 , 35 , 36 ]. BOT OPSCC had a statistically significant higher rate of positive margins when compared to tonsillar OPSCC (28.1% [95% CI 15.1–43.3] vs. 7.5% [95% CI 3.3–13.3]).…”
Section: Resultsmentioning
confidence: 99%
“…A total of 12 studies included extractable data on margin status after resection using TORS [ 12 , 26 , 27 , 28 , 29 , 30 , 31 , 32 , 33 , 34 , 35 , 36 ]. BOT OPSCC had a statistically significant higher rate of positive margins when compared to tonsillar OPSCC (28.1% [95% CI 15.1–43.3] vs. 7.5% [95% CI 3.3–13.3]).…”
Section: Resultsmentioning
confidence: 99%
“…In their 4-year-long surgical series (2014-2018), Huang et al reported that 70% of patients had received adjuvant treatment, and concurrent chemoradiation in almost half of cases 5 . Other authors showed that upfront TOS proved successful in sparing RT in 9-27% of cases and CRT in 34-45% 34,39,40 . Our results agree with literature data, since about 30% of patients were treated with surgery only, because of the lack of pathological risk factors.…”
Section: Discussionmentioning
confidence: 98%
“…Several series have shown that TORS followed by adjuvant (chemo)radiotherapy is associated with inferior quality of life compared to TORS alone 22,23 ; furthermore, a small retrospective series showed that patients with locally advanced oropharyngeal carcinoma treated with TMT including TORS had worse functional outcomes than patients treated with definitive chemoradiotherapy 24 . Most of the evidence for excess toxicity associated with TMT, however, is derived from series that included nonrobotic surgery and/or enrolled patients with HPV‐negative cancers, the latter of which often have more comorbid conditions and are consequently more vulnerable to treatment‐related toxicity 25–29 . To date, there have been no series describing outcomes specifically in patients with HPV + OPSCC who undergo TORS and TMT.…”
Section: Introductionmentioning
confidence: 99%
“…24 Most of the evidence for excess toxicity associated with TMT, however, is derived from series that included nonrobotic surgery and/or enrolled patients with HPV-negative cancers, the latter of which often have more comorbid conditions and are consequently more vulnerable to treatment-related toxicity. [25][26][27][28][29] To date, there have been no series describing outcomes specifically in patients with HPV + OPSCC who undergo TORS and TMT. In this study, we summarize survival outcomes and toxicity in a cohort of patients with HPV + OPSCC who received TMT at a tertiary academic medical center performing a high volume of TORS.…”
Section: Introductionmentioning
confidence: 99%